Proceedings of the XXV International Symposium on Lattice Field Theory — PoS(LATTICE 2007) 2008
DOI: 10.22323/1.042.0178
|View full text |Cite
|
Sign up to set email alerts
|

A QCD chiral critical point at small chemical potential: is it there or not?

Abstract: For a QCD chiral critical point to exist, the parameter region of small quark masses for which the finite temperature transition is first-order must expand when the chemical potential is turned on. This can be tested by a Taylor expansion of the critical surface (m u,d , m s ) c (µ). We present a new method to perform this Taylor expansion numerically, which we first test on an effective model of QCD with static, dense quarks. We then present the results for QCD with 3 degenerate flavors. For a lattice with N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
84
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(95 citation statements)
references
References 12 publications
9
84
2
Order By: Relevance
“…line which terminates in an Ising universality class second order endpoint [22], as illustrated in Fig. 3 (see however [23]). The plasma generated in very high energy heavy ion collisions is expected to follow a trajectory close to the T axis (small µ), which probably misses the phase transition line [24] but may nevertheless experience a rather sharp crossover with a large correlation length.…”
Section: Spectral Function Near the 2'nd Order Transition Pointmentioning
confidence: 94%
“…line which terminates in an Ising universality class second order endpoint [22], as illustrated in Fig. 3 (see however [23]). The plasma generated in very high energy heavy ion collisions is expected to follow a trajectory close to the T axis (small µ), which probably misses the phase transition line [24] but may nevertheless experience a rather sharp crossover with a large correlation length.…”
Section: Spectral Function Near the 2'nd Order Transition Pointmentioning
confidence: 94%
“…In this paper, we address an issue of how the critical end line extends when switching on the chemical potential. An interesting result was reported in [6,12] which explored the imaginary chemical potential approach with the naive staggered fermion action. There it was observed that the critical surface has a negative curvature in the μ direction.…”
Section: Introductionmentioning
confidence: 95%
“…Investigations both in the chiral (m Ñ 0) and quenched (m Ñ ∞) limits are interesting on their own, since they allow to understand the influence of confinement and chiral symmetry breaking on the thermal transition. The structure of the Columbia plot which emerges from studies on very coarse lattices [1,2,3] is qualitatively the same for different formulations and lattice spacings: The order of the phase transition for light and heavy quarks is first order, while it becomes a crossover for intermediate values of the mass. Nevertheless, quite significant discrepancies regarding the position of the Z 2 lines separating these regions have been found using different fermions discretizations and no continuum extrapolation of any feature is available.…”
Section: Introductionmentioning
confidence: 86%
“…In the present study we used a GPU implementation of it present in the CL 2 QCD software, a OpenCL based code which is publicly available 1 and that has been optimised to run efficiently on AMD graphic cards [9]. All our simulations were run on the L-CSC cluster [10] in Darmstadt.…”
Section: Simulation Detailsmentioning
confidence: 99%
See 1 more Smart Citation